A Self-determination theory based intervention to promote healthy eating and physical activity in school-aged children - Girelli, Laura; Luccidi, Fabio (Cuadernos de Psicología del Deporte, 2016)
Childhood overweight and obesity in both girls and boys is reaching epidemic proportions over the world, Italy included. Childhood obesity has been linked to deleterious health consequences. There is a need to develop theory based and cost-effective interventions to promote healthy eating and physical activity with the aim to reduce obesity. The purpose of this study was to evaluate a long-term theory-based intervention to promote healthy lifestyles in underserved school-aged children. A quasi experimental design was adopted, in order to evaluate the effectiveness of the intervention, considering information from their parents. Parents were asked to rate their children attitude, motivation and behavior regarding two energy balance-related behaviors. Results indicate that pupils involved in the intervention were more likely to do physical activity in leisure time and have more positive attitudes toward exercise compared to the control group. About eating habits, children involved in the intervention were more likely to choose healthy foods and less likely to choose fat foods compare to the control group. Changes in attitude and motivation between the baseline and the follow up and the two groups are also shown, even if not significant. Despite several limitations in the design, this study provided further support to the argument that Self-determination theory-based interventions could result in meaningful health-behavior changes.